In vitro dynamics of HIV-1 BF intersubtype recombinants genomic regions involved in the regulation of gene expression - Carobene, Mauricio (2009)
HIV-1 intersubtype recombination is a very common phenomenon that has been shown to frequently affect different viral genomic regions. Vpr and Tat are viral proteins known to interact with viral promoter (LTR) during the replication cycle. This interaction is mainly involved in the regulation of viral gene expression, so, any structural changes in the LTR and/or these regulatory proteins may have an important impact on viral replication and spread. It has been reported that these genetic structures underwent recombination in BF variants widely spread in South America. To gain more insight of the consequences of the BF intersubtype recombination phenomenon on these different but functionally related genomic regions we designed and performed and in vitro study that allowed the detection and recovery of intersubtype recombinants sequences and its subsequent analysis. Our results indicate that recombination affects differentially these regions, showing evidence of a time-space relationship between the changes observed in the viral promoter and the ones observed in the Vpr/Tat coding region. This supports the idea of intersubtype recombination as a mechanism that promotes biological adaptation and compensates fitness variations